Once-told tales : an essay in literary aesthetics - Kivy, Peter; Wiley InterScience (Online service) (Malden, Mass. : Wiley-Blackwell, 2011)
"Drawing comparisons with other art forms, this book examines the role of aesthetic features in silent reading, such as narrative structure, and the core experience of reading a novel as a story rather than a scholarly exercise. Focuses on the experience of the art form known as the novel. Uses the more common perspective of a reader who reads to be told a story, rather than for scholarly or critical analysis. Draws comparisons with experience of the other arts, music in particular. Explores the different effects of a range of narrative approaches."--
"Human beings are captivated by stories. In the modern world we consume fiction as literature, at a huge rate, whether on paper or electronic devices - but what is at the heart of the experience of the novel, of silent reading? Philosophers of art have traditionally focused on a reading experience in which novels are read, re-read, savored, and studied in depth. In this book, Peter Kivy looks at the more common experience of a reader who just reads a novel once, or who, if they do read it again, do so for the same reasons that they read it the first time: to be told a story. This is not the reading experience of the scholar or critic, but that of the average reader, and it represents an engagement with the age-old experience of storytelling that is bound up with the very beginnings of humanity. Drawing comparisons with other art forms, this book examines the role of aesthetic features in silent reading, such as narrative structure, and pursues the experiential core of what it is to read a novel: a tale once-told"--
Machine generated contents note: Preface -- What it's All About -- The Aesthetics of Literature: A Neglected Topic -- The Aesthetic Property: Its Kinds and Its Kind -- The Ethical, the Aesthetic, and the Artistic -- Structure Aesthetics and Novelistic Structure -- Continuous Time and Interrupted Time -- Seeing is Believing -- Reading is Believing -- Twice-Told Tales and More.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Literature -- Aesthestics; Electronic books